2004
DOI: 10.1002/jhet.5570410611
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected formation of 1,2‐dihydro‐2‐azolyl‐and azinylisoquinolines by the reduction of the corresponding isoquinolinium salts with sodium borohydride in methanol

Abstract: Dedicated to Professor Josef Michl on the occasion of his 65 th birthdayThe reduction of different 2-azolyl-and azinylisoquinolinium salts with sodium borohydride in methanol was studied. Surprisingly, contrary to what is found in the literature 1,2-dihydroisoquinoline derivatives were obtained. Their formation was attributed to the electron withdrawing character of the heterocyclic ring in position 2 of the isoquinolinium moiety. This was corroborated by synthesis and reduction of differently substituted 2-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Here, the base potassium carbonate was used to neutralize HBF 4 , the acid produced in this reaction. According to our initial analysis and to the previous report, 15 this reaction might finally give the dihydroisoquinoline derivative 1¢ (Scheme 2a). The ICTB 1a is thought to undergo an insertion reaction with amine 2i, providing an N-aryl isoquinolinium salt.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…Here, the base potassium carbonate was used to neutralize HBF 4 , the acid produced in this reaction. According to our initial analysis and to the previous report, 15 this reaction might finally give the dihydroisoquinoline derivative 1¢ (Scheme 2a). The ICTB 1a is thought to undergo an insertion reaction with amine 2i, providing an N-aryl isoquinolinium salt.…”
supporting
confidence: 54%
“…14 Prauda and coworkers also showed that some N-aryl isoquinolinium salts could be reduced with sodium borohydride in protic solvents to afford dihydroisoquinolines (Scheme 1b). 15 These studies suggested to us that ICTBs (1) might be able to react with amines, generating isoquinoline derivatives through similar addition/reductive-opening/cyclization mechanisms. Following such an idea, we explored the 'formal' one-step transformations of ICTBs into nitrogenous heterocycles, which would be of value in the synthesis of many biologically important alkaloids.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The reduction of 2‐phenylisoquinolinium salts by silanes takes place in an analogous fashion (eq 8). Previous work22–24 has established that attack by nucleophiles and hydride reducing agents occurs at the 1‐position in these compounds. This suggests 17 as the organic product of the reduction of 16 .…”
Section: Resultsmentioning
confidence: 99%